Differences in the processing of short-range apparent motion at small and large displacements. - Snowden, R; Braddick, O (1990)
Using random dot patterns we have compared performance on direction discrimination tasks for single and multi-step sequences of apparent motion at a range of displacement sizes. Performance was measured by varying the correlation between the frames. For "small" displacements we found that no improvement in performance occurs with stimulus duration (number of frames) if the movement of individual elements within the pattern was restricted to one step, whereas if elements undergo multiple steps, performance improves with duration. For "large" displacements, on the contrary, performance improves with increasing stimulus duration irrespective of whether individual elements are restricted to single steps. These results suggest that small and large displacements are processed in different ways. We review possible psychophysical and physiological correlates of this suggestion.